PREDICTING NIV FAILURE IN COPD PATIENTS USING THE SERIAL HACOR SCORE - Noor Safdar; Huma Batool; Muhammad Waseem; Asifa Karamat; Shazia Awan; Abdur Rahman Zaheer (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background:Non-Invasive Ventilation (NIV) is a key therapeutic approach for managing acute respiratory failure in patients with Chronic Obstructive Pulmonary Disease (COPD). However, NIV failure remains a significant clinical challenge, often leading to increased morbidity and mortality. The HACOR score comprising Heart rate, Acidosis, Consciousness level, Oxygenation, and Respiratory rate has emerged as a potential tool to predict NIV failure. This study aimed to evaluate the predictive utility of the HACOR score in COPD patients undergoing NIV in the Intensive Care Unit (ICU) of Gulab Devi Hospital.Objective:To evaluate the effectiveness of the HACOR score in predicting NIV failure in COPD patients admitted to the Intensive Care Unit of Gulab Devi Chest Hospital.Methodology:This was a prospective observational study conducted over six months involving COPD patients admitted with acute respiratory failure who required NIV. HACOR scores were calculated at three time intervals: before initiating NIV, at 1-hour post-initiation, and at 24 hours. Statistical analysis included logistic regression, receiver operating characteristic (ROC) curve analysis, and chi-square testing to examine the association between HACOR scores and NIV outcomes.Results:A total of 109 patients were included. The mean HACOR score was 10.2 (SD±4.5) after 1 hour 7.8 (SD 3.2) and after 24 hours of NIV 6.5 (SD 2.8). Chi-square analysis showed a significant correlation between higher HACOR scores and NIV failure at all-time points (p < 0.05). ROC curve analysis demonstrated good predictive accuracy with AUC values of 0.82 (before NIV),0.78 (1 h post-NIV) and 0.75 (24 h post-NIV). HACOR cut-off values predicting failure were ≥9 before NIV (PPP 0.78; NPP 0.85), ≥7 after 1 hour (PPP 0.75; NPP 0.82), and ≥ 6 after 24 hours (PPP 0.72; NPP 0.80.Conclusion:The HACOR score is a reliable and practical tool for early prediction of NIV failure in COPD patients. Its implementation can aid in risk stratification, allowing timely clinical decisions to optimize NIV use and improve patient outcomes.